RTHP-38. THE FEASIBILITY OF PSYCHOLOGICAL INTERVENTIONS FOR REDUCE THE NEED OF ANESTHESIA DURING RADIOTHERAPY IN < 5 YR PEDIATRIC PATIENTS WITH CNS MALIGNANCIES - Cai, Linbo (Neuro Oncol, 2019)
OBJECTIVES: The aim of this study was to explore the psychological intervention to reduce the use of sedatives in children when undergoing radiotherapy. METHODS: From January 2017 to December 2018, 53 pediatric patients, without limited consciousness, from 3 to 5 years old diagnosed with brain tumors and admitted to radiotherapy at the oncology centers of Guangdong Sanjiu Brain Hospital, received the systematic intervention (including desensitization, simulation play practice, distraction, etc.) to reduce medical fear for radiotherapy. A case-control study of semi-structured and play-based interventions was undertaken for psychological preparation of young children during radiotherapy. RESULTS: After receiving interventions, 49 children were willing to cooperate with treatment, with the success rate of 92.45%. There were 19 children behaving cooperative in the 3-year-old group, while there were both 17 patients showing compliance in the 4-year-old group and 5-year-old group. Compared with the success rate of the 3-year-old group (84.21%), psychological interventions were more appropriate for the 4-year-old group (94.12%) and 5-year-old group (100%). For those failed cases, 2 children aged 3 used anesthesia during the whole radiotherapy sessions; 2 children aged 3 and 4 took sedatives in the early session of radiotherapy. CONCLUSION: This study suggested that psychological intervention was able to improve the adherence of pediatric patients to the whole treatment course and reduce the occurrence of drug resistance due to non-compliance.